Optimizing the Design of Supply Chains for Carbon Capture, Utilization, and Sequestration in Europe: A Preliminary Assessment - d'Amore, Federico; Bezzo, Fabrizio (Frontiers in Energy Research, 2020)
Carbon capture and storage represents a key technology for reducing anthropogenic emissions of greenhouse gases. In addition to this, carbon utilisation has often been considered as a viable option to increase the environmental benefits, while decreasing costs of the mere capture and storage system. This contribution proposes an optimisation framework for the design of carbon capture, transport, utilisation and storage supply chains in the European context. Based on literature data, technologies for CO2 conversion into methanol and polyether carbonate polyols were selected as the most promising ones and incorporated in the optimisation framework. The goal is to reduce 50% of the European emissions from large stationary sources by 2030. Results highlight that, under our assumptions, the significance of carbon utilisation in terms of reduction of the environmental impact is likely to be a minor one: considering the current state of technologies only about 2.4% of the overall CO2 emitted from large stationary sources can be removed by chemical utilisation. However, significant benefits can be obtained in terms of overall cost reduction thanks to revenues deriving from the chemicals being produced.